KARAKTER KEWIRAUSAHAAN MAHASISWA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN (FKIP) UNIVERSITAS RIAU PEKANBARU - Maria Maristella Bago maristella Bsgo; Daeng Ayub Natuna Ayub Natuna; Said Suhil Achmad Suhil Achmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research is motivated by the entrepreneurial character FKIP University student Pekanbaru. The problem was how high the entrepreneurial character mean FKIP UR students. The aim of this study was to determine the level of entrepreneurial character FKIP UR students. The population in this study were 192 students UR department and the study sample was 32 students were taken using quota sampling technique. Instrument of data collection questionnaire with 117 statements and after a stay of 110 tested a valid statement to be made in the research instrument. Data analysis through quantitative descriptive analysis. Instruments used in this study was a questionnaire containing 110 items entrepreneurial character statement FKIP University student Pekanbaru, Riau, with the indicator 1) the commitment and determination, 2) the desire to assume responsibility 3) always seize opportunities, 4) risk-taking is measured, 5) self-esteem, 6) creativity and fleksibelita, 7) desire immediate feedback, 8) high energy levels (energy), 9) are motivated to achieve success, 10) future oriented, 11) the willingness to learn from mistakes, 12) capable lead, 13) diligently, 14) oriented goals, 15) and innovation, 16) knowledgeable. Alternative responses categories for each item statement strongly agree (SS) was scored 5, agree (S) was given a score of 4, less agree (KS) is given a score of 3, disagree (TS) is given a score of 2, and strongly disagree (STS) is given score 1. Keywords: Character, Entrepreneurship, Student.